Wybrane aspekty niemieckich inwestycji w Polsce w kontekście polityki ich cen pozyskiwania - Götz, Marta (Gospodarka w Praktyce i Teorii, 2012)
Germany belongs to major foreign direct investors in Poland. In order to professionally and effectively design and pursue the policy of attracting foreign investors specific knowledge seem indispensable. Firstly, decision makers shall be aware of main peculiarities of direct investments outfl owing from Germany. Secondly, they shall be familiar with some specific pattern of these investments in Poland. Such background may be regarded as a starting point for further steps aiming at attracting foreign capital, specifically the German one. Thus an attempt to identify such regularities.